Northern populations of Finnish raccoon dogs are active at the range edge and unhindered by movement boundaries - Deshpande, Purabi; Toivonen, Pyry; Selonen, Vesa (BioMed Central, 2025)
Studying movements of invasive species is important for controlling their spread into new areas and understanding how their populations can be controlled in the regions where they have already spread. Additionally, animals at the range edge are known to behave differently from those at the range core. Such differences in movement behaviour can further affect the spread of a species into new areas. Here, we use data from GPS tracking of 103 individuals of the invasive raccoon dog (Nyctereutes procyonoides) in Finland to examine the movement of the species. First, we determine whether movement distances differ in the range edge and range core. Next, focusing on dispersing individuals, we explore whether their movements are directional. Finally, we investigate whether the dispersal by raccoon dogs is affected by movement boundaries, such as waterbodies and roads. We show that raccoon dogs at the range edge move larger distances than those in the range core. The dispersing individuals do not show a preference to moving in any particular direction. Finally, we do not find evidence for waterbodies and roads acting as movement boundaries for raccoon dogs. Our results indicate that raccoon dogs are very active at the range edge and highlight how the movement distances of a species might be underestimated if individuals from the invasion front are not studied. The raccoon dog’s spread is likely to continue into favourable habitats and not be hindered by roads or water bodies putting areas at higher latitudes and surrounding countries at the risk of invasion.
Keywords: dispersal; invasion front; invasive species; vieraslajit; mesopredators; vieraspeto